Autoevaluación organizacional basada en la norma ISO 9004:2009: percepciones, comparaciones, preguntas y acciones (2013)
The self-assessment basedon Annex A of the ISO 9004:2009 standard is a very practical diagnostic tool and also very powerful for capturing the image of the organization quickly. It enables to have answers to questions suchas: what are the strengths and weakness of our organization? Do we have adequate processes, resources and competencies to reach our vision and goals? Are we measuring the parameters of importance or not? Do we communicate results adequately? Do we establish priorities to improve that which is aligned with the strategy? On the other hand, like any tool, it has a series of limitations: perceptions of the various members of the organization canbe very different; average score can possibly say very little about the actual situation of the organization, without a careful and open discussion about the extreme perceptions. From the results of 170 self-assessments made by organizations in Holland basedon ISO 9004:2009, some initial conclusions are reached about the application of self-assessment, analyzing the highest and lowest scores achieved. Finally, a series of suggestions and advices are made onhow to prepare, execute and close a self-assessment act.